Risk Management Strategies in Green Supply Chains: Overcoming Barriers in Indian SMEs - Sureshkumar, Vishnu (My University, 2025)
As sustainability pressures unfold with an unprecedented intensity, Indian small and medium-sized enterprises (SMEs) are increasingly challenged to adopt Green Supply Chain Management (GSCM).In this study, the study explores the core internal and external risks that inhibit adoption of GSCM by Indian SMEs, based on an integrated theoretical framework that combines GSCM with supply chain risk management (SCRM). This study uses a qualitative, interpretivist methodological approach and undertakes multiple case studies with five Indian SMEs from various sectors to help contextualize the barriers of financial risk, technology limitations, regulatory ambiguity, and market competition. The study proposes a re-framed typology that defines sustainability risks as either strategic or operational, and highlights resilience strategies as a mediating variable. The study found that while technological advancements and the commitment of leadership can assist as enablers of GSCM, SMEs still lack customized risk models, green financing, and continued regulatory guidance. In conclusion, it will take multi-dimensional support such as policy initiatives, learning and capacity development, collaborative networks, and digital technologies for SMEs to enhance their resilience and maintain competitive advantage in the sustainable supply chain space. Overall, this study examines the theory by converging GSCM and SCRM together and provides insight for policymakers and managers of SMEs working through green transitions in developing economies.
Keywords: fi=Taloustiede|en=Economics|; Master’s Programme in Strategic Business Development